Removal of Selenium and Arsenic Oxyanions Using Natural Goethite-Rich Iron Ore from Daitari, Orissa, India: Effect of Heat Treatment - R.K. Behera; K. Rout; B. Nayak; N.N. Das (Adsorption Science & Technology, 2012)
Sorption capacities of raw and calcined goethite-rich iron ore (GRI) collected from Datari iron-ore mines in Orissa for the removal of As and Se oxyanions were investigated in this study. Thermally treated GRI at 300 °C (GRI-300), having the maximum surface area (49.5 m 2 /g) and pore volume (0.028 cm 3 /g), showed maximum uptake of As(III), As(V) and Se(IV) oxyanions from their aqueous solutions, which progressively decreased when the pH of the solution is increased. At pH 6.0 (approximately), 2.0 g/l GRI-300 dose could remove more than 90% of As(III), As(V) and Se(IV) from their aqueous solutions containing 0.215, 0.265 and 20 mg/l amounts of the compound, respectively. The presence of co-existing ions showed a significant decrease in the uptake of oxyanions by GRI-300 in (PO 4 3– > Cl − > NO 3 − ). The present set of data may be helpful to further asses the potential of readily available GRI to remove different toxic ions from contaminated waters.